A Framework for Assessing the Costs of Pension Reform Reversals - Baksa, Daniel (IMF Working Papers; Working Paper ;, 2020)
Several European countries are currently considering reversing parts of their pension reforms that were adopted previously to improve sustainability. In this paper we present a framework that allows us to quantify the macroeconomic and fiscal costs of such reversals. We thereby integrate the country-specific information from the latest Ageing Report into a dynamic general equilibrium model with overlapping generations. Focusing on Germany and Slovakia as country cases, our model replicates the Ageing Report's pension expenditure projections very well. We calculate the macroeconomic impact of first the additional pension reforms needed to contain the public debt pressures arising from population ageing and second the costs of reform reversals. Our model results show that undoing past pension reforms would generate substantial adverse macroeconomic costs and could pose challenges for fiscal sustainability.